Stigma or Cushion? IMF Programs and Sovereign Creditworthiness - Kai Gehring; Valentin F. Lang (Center for Economic Studies and ifo Institute (CESifo), 2018)
IMF programs are often considered to carry a “stigma” that triggers adverse market reactions. We show that such a negative IMF effect disappears when accounting for endogenous selection into programs. To proxy for a country's access to financial markets, we use credit ratings and investor assessments for 100 countries from 1987 to 2013. Our first identification strategy exploits the differential effect of changes in IMF liquidity on loan allocation. We find that the IMF can “cushion” against falling creditworthiness, despite contractionary adjustments resulting from its programs. A second, event-based strategy using country-times-year fixed effects supports this positive signaling effect. A supplementary text analysis of rating statements validates that agencies perceive IMF programs as positive, particularly when they are associated with reform commitments.
Keywords: E44; F33; F34; G24; 330; International Monetary Fund; sovereign credit ratings; capital market accss; creditworthiness; financial crises